An investigation into the effectiveness of social stories with photograph or symbol illustrations for addressing the specific target behaviours of children with a diagnosis of autism spectrum disorder - Williams, Emily Louise (2011)
This study aimed to investigate the effectiveness of Social Stories utilising either photograph or symbol illustrations to address the target behaviours of children with a diagnosis of Autism Spectrum Disorder (ASD).